Role of adenosine A2A receptors in the loss of consciousness induced by propofol anesthesia. Issue 5 (16th December 2022) - Guo, Meimei; Wang, Jie; Yuan, Yikang; Chen, Lei; He, Jingang; Wei, Wei; Xu, Fuqiang; Liu, Qing; Peng, Mian
Abstract: The mechanism of propofol‐anesthesia‐induced loss of consciousness (LOC) remains largely unknown. We speculated that the adenosine A2A receptor serves as a vital molecular target in regulating LOC states under propofol anesthesia. c ‐Fos staining helped observe the changes in the neuronal activity in the nucleus accumbens (NAc). Initially, the adenosine signals in the NAc were measured under propofol anesthesia using fiber photometry recordings. Then, behavior tests and electrophysiological recordings were used to verify the effect of systemic A2A R agonist or antagonist treatment on propofol anesthesia. Next, the microinjection technique was used to clarify the role of the NAc A2A R under propofol anesthesia. Fiber photometry recordings were applied to assess the effect of A2A R agonist or antagonist systemic treatment on adenosine signal alterations in the NAc during propofol anesthesia. Then, as the GABAergic neurons are the main neurons in the NAc, we further measured the neuronal activity of GABAergic neurons. In our study, propofol anesthesia enhanced the neuronal activity in the NAc, and the adenosine signals were increased in the NAc. SCH58261 reduced the LOC time and sedative depth, while CGS21680 increased those via intraperitoneal injection. Additionally, CGS21680 increased the changes in delta, theta, alpha, beta, and low‐gamma oscillations in the NAc. Moreover, microinjection of SCH58261 significantly shortened the LOC time, whereas microinjection of CGS21680 into the NAc significantly prolonged the LOC duration. The results illustrated that after A2A R agonist administration, the level of extracellular adenosine signals in the NAc was decreased and the neuronal activity of GABAergic neurons was enhanced, whereas after A2A R antagonist administration via intraperitoneal injection, the opposite occurred. This study reveals the vital role of the A2A R in propofol‐induced LOC and that the A2A R could affect the maintenance of propofol anesthesia. Abstract : In this study, the mechanism of A2A R‐mediated loss of consciousness (LOC) under propofol anesthesia was proposed and explored. The A2A R antagonist reduced the LOC induced by propofol anesthesia with a decreased level of adenosine signals in the NAc. Increased extracellular adenosine and prolonged LOC time were measured under A2A R agonist administration. This study provides a potential target for investigating the mechanism of propofol anesthesia.